2018
DOI: 10.3102/0162373718781960
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Effects on Chilean Children’s Achievement Growth: A Cross-Classified Multiple Membership Accelerated Growth Curve Model

Abstract: This study investigates school effects on primary school students' language and mathematics achievement trajectories in Chile, a context of particular interest given its large between-school variability in educational outcomes. The sample features an accelerated longitudinal design (three time-points, four cohorts) together spanning Grades 3 to 8 (n = 19,704 students in 156 schools). The magnitudes of school effects on students' growth trajectories were found to be sizeable (generally larger than school effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 99 publications
(137 reference statements)
1
1
0
1
Order By: Relevance
“…More research on teacher effects and instructional processes at the classroom level could help to disentangle the large school effects observed in this context, as numerous international studies have found greater between-classroom than between-school variance in student achievement (Hill & Rowe, 1996;Luyten, 2003) and a large proportion of these classroom-level variance to be explained by what teachers do in the classroom (Muijs & Reynolds, 2011;Muijs et al, 2014). Furthermore, an extension of the present study was also able to confirm that teacher effects on students' language and mathematics achievement growth in Chile are large (54-66%) and exceed the remaining school effects (21% and 30%) (Ortega, Malmberg, & Sammons, 2017).…”
Section: Discussionsupporting
confidence: 68%
“…More research on teacher effects and instructional processes at the classroom level could help to disentangle the large school effects observed in this context, as numerous international studies have found greater between-classroom than between-school variance in student achievement (Hill & Rowe, 1996;Luyten, 2003) and a large proportion of these classroom-level variance to be explained by what teachers do in the classroom (Muijs & Reynolds, 2011;Muijs et al, 2014). Furthermore, an extension of the present study was also able to confirm that teacher effects on students' language and mathematics achievement growth in Chile are large (54-66%) and exceed the remaining school effects (21% and 30%) (Ortega, Malmberg, & Sammons, 2017).…”
Section: Discussionsupporting
confidence: 68%
“…The research on educational effectiveness has shown that a significant proportion of the variation in students’ outcomes is located at the classroom level and can be explained by process variables (Muijs et al, 2014; Ortega, Malmberg, & Sammons, 2018b). These process variables correspond to quality of teaching and classroom interaction indicators that are generally obtained through teacher self-reporting, teacher evaluations completed by their students or systematic classroom observation.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…La investigación sobre efectividad educativa ha demostrado que una proporción significativa de la variación en los resultados de los estudiantes se ubica a nivel de aula y puede explicarse por variables de proceso (Muijs et al, 2014; Ortega, Malmberg, & Sammons, 2018b). Estas variables de proceso corresponden a indicadores de calidad de la enseñanza y de las interacciones en el aula, que generalmente se obtienen a través del auto-reporte de los docentes, de la evaluación de docentes por parte de los alumnos o de observaciones sistemáticas del aula.…”
Section: Marco Conceptualunclassified